Measuring color capability of wide color gamut near‐eye displays. Issue 5 (11th May 2021) - Penczek, John; Austin, Richard L.; Hasan, Monirul; Smith, Euan
Abstract: Near‐eye displays often use narrow spectral bandwidth light sources to create virtual images. These sources provide wider color gamuts. However, the measurement instrument's spectral bandwidth and spectral stray light need to be considered. We evaluate these aspects in characterizing the display's color capability. Abstract : As many display technologies continue their advance toward wider color gamuts, this study evaluates how the characteristics of spectroradiometers influence our ability to accurately measure those gamuts.